Navigating global fashion policy: labor, environment, and future directions for sustainability - Meital Peleg Mizrachi (Academia Environmental Sciences and Sustainability)
In the past decade, numerous policies and regulations have emerged to promote sustainable fashion, addressing both environmental and social issues across textile, clothing, footwear, and leather value chains. Key initiatives include the Bangladesh Accord, the Organization for Economic Co-operation and Development (OECD) Due Diligence Guidance for Responsible Supply Chains, California’s SB62 law, and the Uyghur Forced Labor Prevention Act. Proposed measures, such as France’s fast-fashion tax and the New York Fashion Sustainability and Social Accountability Act, further highlight the growing recognition of fashion's impacts. This regulatory wave reflects increasing awareness of the fashion industry’s environmental and social consequences, alongside evolving geopolitical and economic dynamics, particularly trade relations among China, the United States, and Europe. These complexities are exemplified by the shift from Europe-led fast fashion to China-driven ultra-fast fashion. This article reviews global policies and legislative efforts aimed at sustainable fashion, examining initiatives such as the E.U. Strategy for Sustainable and Circular Textiles and the Americas Trade and Investment Act. It emphasizes the critical influence of political contexts and externalities on shaping outcomes, particularly given the limitations of industry self-regulation. The study concludes that effective policies must integrate environmental and social criteria, balance global and local priorities, and remain adaptable to diverse socioeconomic and cultural contexts. Policymakers should ensure equitable, clear frameworks to address the interconnected challenges of labor rights, environmental sustainability, and economic development within the fashion industry.